mito-TEMPO Attenuates Oxidative Stress and Mitochondrial Dysfunction in Noise-Induced Hearing Loss via Maintaining TFAM-mtDNA Interaction and Mitochondrial Biogenesis - Chen, Jia-Wei; Ma, Peng-Wei; Yuan, Hao; Wang, Wei-Long; Lu, Pei-Heng; Ding, Xue-Rui; Lun, Yu-Qiang; Yang, Qian; Lu, Lian-Jun (Frontiers in Cellular Neuroscience, 2022)
The excessive generation of reactive oxygen species (ROS) and mitochondrial damage have been widely reported in noise-induced hearing loss (NIHL). However, the specific mechanism of noise-induced mitochondrial damage remains largely unclear. In this study, we showed that acoustic trauma caused oxidative damage to mitochondrial DNA (mtDNA), leading to the reduction of mtDNA content, mitochondrial gene expression and ATP level in rat cochleae. The expression level and mtDNA-binding function of mitochondrial transcription factor A (TFAM) were impaired following acoustic trauma without affecting the upstream PGC-1α and NRF-1. The mitochondria-target antioxidant mito-TEMPO (MT) was demonstrated to enter the inner ear after the systematic administration. MT treatment significantly alleviated noise-induced auditory threshold shifts 3d and 14d after noise exposure. Furthermore, MT significantly reduced outer hair cell (OHC) loss, cochlear ribbon synapse loss and auditory nerve fiber (ANF) degeneration after the noise exposure. In addition, we found that MT treatment effectively attenuated noise-induced cochlear oxidative stress and mtDNA damage, as indicated by DHE, 4-HNE and 8-OHdG. MT treatment also improved mitochondrial biogenesis, ATP generation and TFAM-mtDNA interaction in the cochlea. These findings suggest that MT has protective effective against NIHL via maintaining TFAM-mtDNA interaction and mitochondrial biogenesis based on its ROS scavenging capacity.